The slipper and the rose [videorecording (DVD)] : the story of Cinderella - Forbes, Bryan, 1926-2013; Chamberlain, Richard, 1935-; Craven, Gemma, 1950-; Crosbie, Annette, 1934- (Shout Factory, 2019)
A lavish retelling of the classic Cinderella fairy tale.